Sport Student Statistical Reasoning Ability as the Outcomes of Statistical Reasoning Learning Environment - Nidaul Hidayah; Mona Fiametta Febrianty; Fitri Rosdiana (Universitas Pendidikan Indonesia, 2022)
This research aimed to describe the quality of sports student Statistical Reasoning Ability (SRA) through the Statistical Reasoning Learning Environment (SRLE). This research employed a qualitative analysis. The qualitative analysis was carried out using the grounded theory method. The research subjects were 29 Sports Coaching Education Study Program students receiving SRLE learning. The research finding shows that there are five categories to describe the quality of sports student Statistical Reasoning Ability: problem understanding, concept mastery, argument validity, well-ordered thinking process, and interpretation accuracy.